Heritable changeability: Epimutation and the legacy of negative definition in epigenetic concepts. (April 2021) - Le Goff, Anne; Allard, Patrick; Landecker, Hannah
Abstract: Epigenetic concepts are fundamentally shaped by a legacy of negative definition, often understood by what they are not. Yet the function and implication of negative definition for scientific discourse has thus far received scant attention. Using the term epimutation as exemplar, we analyze the paradoxical like-but-unlike structure of a term that must simultaneously connect with but depart from genetic concepts. We assess the historical forces structuring the use of epimutation and like terms such as paramutation. This analysis highlights the positive characteristics defining epimutation: the regularity, oxymoronic temporality, and materiality of stable processes. Integrating historical work, ethnographic observation, and insights from philosophical practice-oriented conceptual analysis, we detail the distinctive epistemic goals the epimutation concept fulfils in medicine, plant biology and toxicology. Epimutation and allied epigenetic terms have succeeded by being mutation-like and recognizable, yet have failed to consolidate for exactly the same reason: they are tied simultaneously by likeness and opposition to nouns that describe things that are assumed to persist unchanged over space and time. Moreover, negative definition casts the genetic-epigenetic relationship as an either/or binary, overshadowing continuities and connections. This analysis is intended to assist practitioners and observers of genetics and epigenetics in recognizing and moving beyond the conceptual legacies of negative definition. Highlights: Negative definition has played a key role in the delimitation and instability of epigenetic concepts. Negatively defined epigenetic concepts must paradoxically be analogous to – but also the opposite of – genetic phenomena. Epimutation is valued in various explanatory contexts because of its simultaneous adjacency to but distinction from mutation. The legacy of negative definition fails to capture the heritable changeability that positively defines epigenetic events. Like-but-unlike constraints trap concepts such as epimutation in an epigenetic/genetic binary structure.